Flexible Jobs Make Parents Happier: Evidence from Australia - Shuye Yu; Agnieszka Postepska (Institute of Labor Economics (IZA), 2020)
Recent studies have found that self-reported life satisfaction drops during the transition into parenthood which has been mainly attributed to work-family conflict. This study investigates whether different forms of flexible employment can alleviate this drop in parental life satisfaction during this period. A fixed-effects analysis in an event study framework using Australian household survey data (HILDA) delivers convincing evidence that working flexibly indeed alleviates the drop in subjective well-being suggesting that it relieves the stress related to work-family conflict. Moreover, we find substantial gender heterogeneity in the effects different types of flexible employment have on mothers and fathers. Mothers with short part-time jobs (0-20 hours per week) exhibit greater life satisfaction than mothers who work full-time, especially when their children are younger than 4 years old. Among fathers, self-scheduling and home-based work yield a significant increase in perceived happiness as compared to fixed employment terms. This is especially true for fathers of one- and two-years-olds. These results are consistent with a typical intra-household time allocation of parents in Australia.
Keywords: D1; I31; J13; J16; J21; 330; work and family; transition to parenthood; subjective well-being; flexible work